Multilayered tournaments - Junichiro Ishida (Osaka University, Institute of Social and Economic Research (ISER), 2013)
In many facets of life, we often face competition with a multilayered structure in which different levels of competition take place simultaneously. In this paper, we propose a new class of tournament models, called multilayered tournaments, to capture this type of competitive environment. Among other things, we find that: (i) an increase in individual incentives, holding the level of team incentives fixed, can lower total effort as it induces inefficient allocation of effort; (ii) the optimal level of individual incentives depends on and is complementary to the level of team incentives. The analysis illuminates the essential role of economic subgroups, such as firms, in achieving some degree of cooperation in an inherently competitive environment, and provides an explanation for why high-powered incentives are more common in market arrangements than within firms.
Keywords: D82; D86; 330; Tournaments; Cooperation; Competition; Multi-task problem; Sabotage